Segmental bioimpedance in pregnant end stage renal failure patient for dry weight titration and volume management (case report) - Sabrina Haroon; Jia Neng Tan; Titus Lau; Shiao-Yng Chan; Andrew Davenport (BMC Nephrology, 2023)
Abstract Background Volume assessment, dry weight titration, and blood pressure control in pregnant kidney failure patients are often challenging, with physiological fluid accumulation in the trunk and lower limbs and an increased risk of preeclampsia. We used segmental bioimpedance in the volume management of our kidney failure patient on haemodialysis. Case presentation We report a case of a female patient on maintenance haemodiafiltration with no residual kidney function for whom we used segmental bioimpedance to guide dry weight adjustment. At different gestational periods, we targeted a different extracellular to total body water ratio according to body segments. This allowed us to support her high-risk pregnancy, identify her as probably developing preeclampsia and trigger a plan for closer monitoring and delivery during the third trimester when she had rapid weight gain. Conclusion Segmental bioimpedance is a practical, simple, and non-invasive test that can be performed at the dialysis unit and is useful as an adjunct decision-making tool in the management of pregnant dialysis patients.